The effect of directed reading-thinking activity on achievement in reading comprehension of secondary students with learning disabilities in Lagos state, Nigeria (2010)
A student’s abilitiy to read and understand written texts is one of the fundamental skills that enable students to succeed in his academics. However, far many students in Nigerian schools with learning disabilities reading comprehension is the major deficiency. This study, investigated the effectiveness of the Directed Reading Thinking Activity (DRTA) in improving reading comprehension of secondary students with learning disabilities. The study employed a pre-test, post-test, control group, quasi-experimental research design. The design utilised a 2x2x2 factorial layout. Simple random sampling technique was used to select One Hundred (100) Junior Secondary Class 2 from two junior public schools. The presence of different levels (ranging from mild to severe) of learning disabilities was the major criterion far this selection. Screening was conducted with the Myklebust Rating Scale (r = 0.76). Participants in the experimental group were exposed to five weeks of reading comprehension training using the directed reading thinking activity strategy. The control group was not treated. Three null hypotheses were formulated, while data collected were analysed using t-test statistics. The results showed that participants exposed to the directed reading thinking activity strategy performed better than their counterparts in the control group. Thus, since the directed reading thinking activity strategy was found to be superior to the conventional method.